Bibliometric Analysis: Problem-Based Learning, Problem-Solving Skills, Self-Regulated Learning Assisted by Geogebra in Vocational High School - Setyani, Arie; Masrukan; Kurniasih, Ary Woro (Universitas Tidar, 2025)
This study aims to analyze the bibliometric mapping of vocational high school mathematics research from 2020 to 2024 to address the research gap on problem-solving skills in the problem-based learning model assisted by GeoGebra, with a focus on students’ self-regulated learning in vocational high school. The data collected focuses on the keywords